Measurement and Determinants of Access to Loans - Christa Hainz; Tatjana Nabokin (Center for Economic Studies and ifo Institute (CESifo), 2013)
Measuring and identifying financial constraints represents an important challenge in empirical studies. Due to data limitations perception-based indicators or approximations of access to finance by the usage of finance are often used, disregarding firm-specific differences in the demand for external finance. Using unique firm-level survey data, which provide information on a firm's credit demand, we develop a direct measurement for access to credit and provide for the first time an empirical evaluation of these methods. We find that information on the usage of credit is not sufficient to identify financially constrained firms, while perception based indicators are surprisingly precise. The paper concludes by presenting recommendations for future survey design.
Keywords: G21; O16; 330; access to finance; usage of finance; credit demand; perceived access to finance